Co-creating an integrated curriculum alongside community partners: a creative analytic approach. Issue 3 (3rd July 2019) - Boluk, Karla; Muldoon, Meghan; Johnson, Corey
ABSTRACT: Traditional approaches to university education are not effective. Problematically, the emphasis in education is teaching rather than the ability for students to learn . Recognising the constraints of traditional instruction, we assembled a collegial team exploring a creative pedagogical tool to co-instruct and co-learn from our practice. Specifically, our contribution explores our process of co-creating an Integrated Curriculum Design (ICD) project together with our community partners. Our ICD reflects our response to a concern brought forward by a local Destination Marketing Organisation, and was mutually informed by professors, graduate students, and adapted based on the feedback of our undergraduate students, and iterative consultation with our community partners. We employ Creative Analytic Practice (CAP) as a series of vignettes to aid in our understanding of how we co-created our ICD model and the value it has generated for all those involved, pausing at a scholarly-community intersection to reflect on opportunities in co-creating tourism pedagogy with an array of scholarly and community partners.